Genomic profiling of multifocal intrahepatic cholangiocarcinoma reveals intraindividual concordance of genetic alterations. (17th November 2020) - Lee, Sung Hwan; Simoneau, Eve B; Karpinets, Tatiana; Futreal, P Andrew; Zhang, Jianjun; Javle, Milind; Zhang, Jianhua; Vauthey, Jean-Nicolas; Lee, Ju-Seog; Estrella, Jeannelyn S; Chun, Yun Shin
Abstract: In multifocal intrahepatic cholangiocarcinoma (IHC), intrahepatic metastases (IM) represent a contraindication to surgical resection, whereas satellite nodules (SN) do not. However, no consensus criteria exist to distinguish IM from SN. The purpose of this study was to determine genetic alterations and clonal relationships in surgically resected multifocal IHC. Next-generation sequencing of 34 spatially separated IHC tumors was performed using a targeted panel of 201 cancer-associated genes. Proposed definitions in the literature were applied of SN located in the same liver segment and ≤2 cm from the primary tumor; and IM located in a different liver segment and/or >2 cm from the primary tumor. Somatic point mutations concordant across tumors from individual patients included BAP1, SMARCA4 and IDH1 . Small insertions and deletions (indels) present at the same genome positions among all tumors from individuals included indels in DNA repair genes, CHEK1, ERCC5, ATR and MSH6 . Copy number alterations were also similar between all tumors in each patient. In this cohort of multifocal IHC, genomic profiles were concordant across all tumors in each patient, suggesting a common progenitor cell origin, regardless of the location of tumors in the liver. The decision to perform surgery should not be based upon a perceived distinction between IM and SN. Abstract : Multiple intrahepatic tumors in intrahepatic cholangiocarcinoma are classified as satellite nodules or metastases, based on tumor location in the liver. In this study, genomic profiles were concordant across all tumors in individual patients, indicative of monoclonal metastatic seeding.